Sustainability standards for patrimonial housing in the Historic Center of Cuenca - Ecuador - Espinoza Mosquera, José Luis; Quesada Molina, Felipe; Calle Pesántez, Andrea Estefanía; Ortiz Fernández, Jessica Mariela (Estoa. Journal of the Faculty of Architecture and Urbanism, 2019)
The aim of the study is to analyze the standards of energy efficiency and quality of the indoor environment of the heritage dwellings in the Historic Centre of Cuenca, considering the following factors: energy consumption, temperature, indoor air quality, natural lighting and acoustic comfort. The methodology used is mixed and of longitudinal design, involving quantitative and qualitative variables for the evaluation of environmental and electrical measurements, as well as the perceptions of comfort of the occupants of the houses. In a first stage, a survey is carried out to 280 houses in Cuenca to determine energy consumption habits and indoor environment conditions; in a second phase, a monitoring of electrical and environmental variables is carried out in three houses with patrimonial characteristics, through the use of measurement sensors, simulations and perception surveys. Subsequently, the results are analyzed and evaluated in order to compare them with energy efficiency and indoor environment quality standards of national and international standards, determining results that demonstrate that users adapt to comfort conditions different from those established by standards, such as temperature, where users, in response to the Andean climate, admit lower ranges than the established standards.